Prospect of potential intrauterine programming impacts associated with COVID-19 - Khanal, Prabhat; Duttaroy, Asim K. (Frontiers in Public Health, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) - 2019 (COVID-19) has led to a worldwide public health concern. In addition to immediate impacts on human health and well-being, COVID-19 can result in unfortunate and long-term health consequences for future generations. In particular, pregnant women and the developing fetuses in low-income settings could be prone to a higher risk of undernutrition, often due to an inadequate supply of food and nutrition during a pandemic outbreak like COVID-19. Such situations can subsequently lead to an increased risk of undesirable health consequences, such as non-communicable diseases including obesity, metabolic syndrome, hypertension, and type 2 diabetes, in the individuals born to exposed mothers via fetal programming. Moreover, COVID-19 infection or related stress during pregnancy can induce long-term programming outcomes on neuroendocrinological systems in offspring after birth. However, the long-lasting consequences of the transplacental transmission of COVID-19 in offspring are currently unknown. Here we hypothesize that a COVID-19 pandemic triggers intrauterine programming outcomes in offspring due to multiple maternal factors (e.g., nutrition deficiency, stress, infection, inflammation) during pregnancy. Thus, it is crucial to establish an integrated lifetime health information system for individuals born in or around the COVID-19 pandemic to identify those at risk of adverse pre-and postnatal nutritional programming. This approach will assist in designing specific dietary or other nutritional interventions to minimize the potential undesirable outcomes in those nutritionally programmed individuals.